PENERAPAN METODE MODELLING UNTUK MENINGKATKAN KEMAMPUAN MENGGOSOK GIGI PADA ANAK DOWN SYNDROME KELAS I DI SLB YPAC MAKASSAR - Akbar, Akbar; Saleh, Wizerti Ariastuti; Faizal, Faizal (JURNAL ORTO DIDAKTIKA, 2025)
ABSTRACT The problem of this research is that Down Syndrome children at SLB YPAC Makassar are not yet able to brush their teeth appropriately and correctly independently. The formulation of the research problem is